2012
DOI: 10.5599/jese.2012.0021
|View full text |Cite
|
Sign up to set email alerts
|

On the suppression of cathodic hypochlorite reduction by electrolyte additions of molybdate and chromate ions

Abstract: The goal of this study was to gain a better understanding of the feasibility of replacing Cr(VI) in the chlorate process by Mo(VI), focusing on the cathode reaction selectivity for hydrogen evolution on steel and titanium in a hypochlorite containing electrolyte. To evaluate the ability of Cr(VI) and Mo(VI) additions to hinder hypochlorite reduction, potential sweep experiments on rotating disc electrodes and cathodic current efficiency (CE) measurements on stationary electrodes were performed. Formed electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 13 publications
(25 reference statements)
5
32
0
Order By: Relevance
“…The validation tests were run with four cells for 19 days with one power shutdown before the evaluation of the performance. The cathodic current efficiency was determined to be 97.2 ± 0.4% which is well in line with the work of Gustavsson et al [20] as well as Spasojevi´c et al [7]. The cell voltage was 3.135 ± 0.015 V at a current density of 2 kA m -2 .…”
Section: Validation Of Testing Equipmentsupporting
confidence: 88%
See 2 more Smart Citations
“…The validation tests were run with four cells for 19 days with one power shutdown before the evaluation of the performance. The cathodic current efficiency was determined to be 97.2 ± 0.4% which is well in line with the work of Gustavsson et al [20] as well as Spasojevi´c et al [7]. The cell voltage was 3.135 ± 0.015 V at a current density of 2 kA m -2 .…”
Section: Validation Of Testing Equipmentsupporting
confidence: 88%
“…Stability tests and validation trials were made in the test pilot unit with titanium cathodes since they have proven to be stable and give high faradaic yields [20,22]. The validation tests were run with four cells for 19 days with one power shutdown before the evaluation of the performance.…”
Section: Validation Of Testing Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in the present paper, a complete coverage of the substrate is required to fully block the hypochlorite reduction. This is also supported by results obtained for polished titanium and steel substrates, where it was shown that μM levels of chromate efficiently suppress hypochlorite reduction . However, in the commercial chlorate process, concentrations between 2–8 gL −1[48–49] are required to obtain 90–95% cathodic current efficiency .…”
Section: Resultsmentioning
confidence: 99%
“…However, sodium dichromate is listed in the Annex XIV under REACH [18], which means that without authorization it is forbidden to use after the sunset date in late 2017. Efforts have been made to exchange chromium with molybdenum, yttrium and other rare earth metals but so far nothing has proven good or long-term stable enough to replace chromate [19][20][21][22][23]. Recently, it was shown that adding trivalent chromium to the electrolyte will be sufficient to in situ form the desired species [24].…”
Section: Introductionmentioning
confidence: 99%